1995
DOI: 10.1172/jci117835
|View full text |Cite
|
Sign up to set email alerts
|

An inherited bleeding disorder linked to a defective interaction between ADP and its receptor on platelets. Its influence on glycoprotein IIb-IIIa complex function.

Abstract: Much discussion has concerned the central role of ADP in platelet aggregation. We now describe a patient (M. L.) with an inherited bleeding disorder whose specific feature is that ADP induces a limited and rapidly reversible platelet aggregation even at high doses. Platelet shape change and other hemostatic parameters were unmodified. A receptor defect was indicated, for, while epinephrine normally lowered cAMP levels of PGE,-treated (M. L.) platelets, ADP was without effect. The binding of [3H12-methylthio-AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
204
0
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(215 citation statements)
references
References 45 publications
(20 reference statements)
9
204
0
2
Order By: Relevance
“…In the 1980s, by the use of 2-azido-ADP that could be photoactivated [94] and also a strong aggregating ADP analogue, 2-methylthioadenosine labelled with 32 P (2-MeS-ADP), Macfarlane and colleagues [95] obtained values ranging from 400 to 1,200 sites per platelet for the receptor that inhibits adenylyl cyclase (P2Y 12 ). More recently, using the latter analogue, Gachet et al [96] reported 600±125 specific binding sites per platelet, and Nurden and co-workers [97] found 826±126 per platelet. Both these latter two groups described patients with low numbers of these binding sites who exhibited a congenital impairment of ADP-induced platelet aggregation, but normal shape change.…”
Section: Binding Sites For Adp On Plateletsmentioning
confidence: 96%
“…In the 1980s, by the use of 2-azido-ADP that could be photoactivated [94] and also a strong aggregating ADP analogue, 2-methylthioadenosine labelled with 32 P (2-MeS-ADP), Macfarlane and colleagues [95] obtained values ranging from 400 to 1,200 sites per platelet for the receptor that inhibits adenylyl cyclase (P2Y 12 ). More recently, using the latter analogue, Gachet et al [96] reported 600±125 specific binding sites per platelet, and Nurden and co-workers [97] found 826±126 per platelet. Both these latter two groups described patients with low numbers of these binding sites who exhibited a congenital impairment of ADP-induced platelet aggregation, but normal shape change.…”
Section: Binding Sites For Adp On Plateletsmentioning
confidence: 96%
“…ADP is an important component of the platelet-dense granules and also an important platelet agonist that stimulates platelets by acting on the G q -coupled P2Y 1 receptor and G i -coupled P2Y 12 receptor. 2,3 Once released, it amplifies the primary responses of other agonists such as collagen and thrombin, leading to enhanced platelet aggregation and stability of the thrombus.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Once released, it amplifies the primary responses of other agonists such as collagen and thrombin, leading to enhanced platelet aggregation and stability of the thrombus. 4,5 It is now well established that concomitant signaling through G q -coupled P2Y 1 and G i -coupled P2Y 12 is necessary and sufficient for the integrin GPIIb/IIIa activation. 3 Furthermore, selective G i activation, when coupled with selective G 12/13 stimulation, also results in platelet aggregation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations